Integrative bioinformatics identifies postnatal lead (Pb) exposure disrupts developmental cortical plasticity - Milo R. Smith; Priscilla Yevoo; Masato Sadahiro; Christine Austin; Chitra Amarasiriwardena; Mahmoud Awawda; Manish Arora; Joel T. Dudley; Hirofumi Morishita (Scientific Reports, 2018)
Abstract Given that thousands of chemicals released into the environment have the potential capacity to harm neurodevelopment, there is an urgent need to systematically evaluate their toxicity. Neurodevelopment is marked by critical periods of plasticity wherein neural circuits are refined by the environment to optimize behavior and function. If chemicals perturb these critical periods, neurodevelopment can be permanently altered. Focusing on 214 human neurotoxicants, we applied an integrative bioinformatics approach using publically available data to identify dozens of neurotoxicant signatures that disrupt a transcriptional signature of a critical period for brain plasticity. This identified lead (Pb) as a critical period neurotoxicant and we confirmed in vivo that Pb partially suppresses critical period plasticity at a time point analogous to exposure associated with autism. This work demonstrates the utility of a novel informatics approach to systematically identify neurotoxicants that disrupt childhood neurodevelopment and can be extended to assess other environmental chemicals.